2010
DOI: 10.1248/bpb.33.379
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrazine-Induced Inactivation of Glyceraldehyde-3-phosphate Dehydrogenase

Abstract: Reactive oxygen species (ROS) can cause oxidative damage to DNA, proteins, and lipids in all living organisms, and the resulting oxidative damage may play roles in several human disorders as well as the aging process.1) Dihydropyrazine (DHP) is produced as a Maillard reaction intermediate by condensation of two molecules of D-glucosamine, 2) and some DHP derivatives generate various radical species and ROS that cause DNA strand cleavage in vitro.3) Since many pyrazine derivatives have been detected in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…2). Consistent with this, in our previous study, Cyclohexyl-DHP exhibited more potent inhibition of GAPDH than that of methyl derivative of DHP (Takechi et al, 2010). Regarding GSH consumption, however, there were no apparent differences in reactivity with GSH between Cyclohexyl-DHP and Me-DHP-3 (Figs.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…2). Consistent with this, in our previous study, Cyclohexyl-DHP exhibited more potent inhibition of GAPDH than that of methyl derivative of DHP (Takechi et al, 2010). Regarding GSH consumption, however, there were no apparent differences in reactivity with GSH between Cyclohexyl-DHP and Me-DHP-3 (Figs.…”
Section: Resultssupporting
confidence: 89%
“…We recently reported that DHP derivatives caused inhibition of GAPDH and that SH-compounds suppressed the inhibition of GAPDH by DHP (Takechi et al, 2010). Therefore, we examined the interaction between DHP and GSH, which is the major intracellular thiol compound in organisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still not known whether a protein or a gene is the target of the radical species. The inhibition effect 20,29) of DHPs on SH-enzymes has only been revealed recently. Further work is needed to elucidate the mechanism of action of DHPs in vitro and in vivo.…”
Section: +mentioning
confidence: 99%
“…Among DHPs that have been studied, the strength order of both DNA strand-breakage activity and biological effects such as lethality and mutagenesis for Escherichia coli indicate a clear difference based on their structures. 19,20) In this report, free radical species from DHPs were identified and examined in order to clarify the radical's participation in the effects of DHPs.…”
mentioning
confidence: 99%